Interrogation as a Way of Studying the Identity of a Minor Who Committed a Crime - S. E. Timoshenko (Сибирское юридическое обозрение)
The article presents the issues aimed at the implementation of the requirements of the criminal and criminal procedure laws on the study of the person who committed the crime as an integral system of its interrelated properties, qualities, features. Along with the identification of sources of relevant information and the use of certain methods of its study, an important component of the activity under consideration is the definition of ways of collecting characterizing information.The article describes the semantics of the word “method”, examines the use of this method of studying the identity of a minor who committed a crime, as the production of interrogation. The Author highlights the problem of insufficiency and (or) unreliability of information about the identity of the juvenile brought to criminal responsibility, including those obtained during interrogation and confrontation. Possibilities of application of methods of conversation and supervision for the purpose of studying of the personality of the teenager at production of his interrogation are revealed. It lists the subjects who may have a particular set of information about the perpetrator of the crime, as well as a list of questions that must be put to them in the course of their interrogation.